Differential prognosis of patients that are candidates for standard, short or prolonged dual antiplatelet treatment discharged after an acute coronary syndrome. Issue 224 (April 2023) - Cordero, Alberto; Escribano, David; García-Acuña, José Mª.; Alvarez-Alvarez, Belén; Cid-Alvarez, Belén; Rodriguez-Mañero, Moisés; Agra-Bermejo, Rosa; Quintanilla, Mª. Amparo; Zuazola, Pilar; González-Juanatey, José R.
Abstract: Background: Current evidence supports the efficacy of prolonged dual antiplatelet treatment (DAPT) for patients at high-ischemic risk and low bleeding risk as well as the efficacy and safety of short DAPT in high-bleeding risk (HBR) patients. Methods: We evaluated patterns of DAPT candidates in all patients discharged in 2 hospitals after an acute coronary syndrome (ACS). Patients categorized in 3 groups: 1) short-DAPT candidates if they met 1 major o 2 minor criteria for HBR, by the 2019 ARC-HBR criteria; 2) prolonged-DAPT candidates if were not HBR and had recurrent ACS, complex percutaneous coronary interventions or diabetes; 3) standard 12 months DAPT if were not include in the previous 2 groups. Major bleeding (MB) was registered according to 3 or 5 of the BARC consortium definitions. Results: We included 8252 patients and 3215 (39 %) were candidates for abbreviated DAPT, 3119 (37.8 %) for prolonged DAPT, and 1918 (23.2 %) for 12 m DAPT. Relevant differences were observed between the 3 categories beyond the bleeding risk. Median follow-up was 57 months. Multivariate analysis identified higher risk of all-cause mortality (HR: 1.96 95 % CI 1.45–2.67; p < 0.001), cardiovascular mortality (HR: 2.10 95 % CI 1.39–3.19; p < 0.011), MACE (HR: 1.69 95 % 1.50–2.02; p < 0.001) and MB (sHR: 3.41 95 % CI 1.45–8.02; p = 0.005) in candidates to short DAPT. Candidates to prolonged DAPT had higher risk of MACE (HR: 1.17 95 % CI 1.02–1.35; p = 0.027). Conclusions: Almost two thirds of patients discharged after an ACS would be candidates for short or prolonged DAPT and these patients are at higher risk of MACE and mortality. Graphical abstract: Unlabelled Image Highlights: Among 8252 patients 39 % were candidates for abbreviated DAPT and 37.8 % for prolonged DAPT. The candidate to abbreviated DAPT had higher risk of all-cause (HR: 1.96) and cardiovascular (HR: 2.10) mortality. Patients' candidate to short or prolonged DAPT had higher risk of MACE. Candidates to abbreviated DAPT had higher risk of MB (sHR: 2.84).